Uma reflexão sobre a saúde mental dos estudantes de Medicina: importância do exercício físico durante a graduação e ação das atléticas no meio universitário - Carrijo, Gabriel Rodrigues (Universidade Federal de São Carlos, 2020)
The aim of this study was to reflect and review the role and benefits of sports and athletics in the universities, especially among Medical students who presents with high rates of psychological disorders. It was carried out through the author’s personal experiences as well as the review of scientific articles. The literature presents the importance of sports for improving the academic performance and as a protective factor to psychological diseases. This highlights the role of athletics associations in universities, which are the main stimulus for the physical activity.
A reflection on the mental health of medical students: the importance of physical exercise during graduation and the action of athletes in the university environment
Keywords: Atividade física; Esporte; Saúde mental; Estudantes; Medicina; Estudantes de medicina; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO